Effects of Increasing Copper from Tri-basic Copper Chloride or a Copper-Amino Acid Complex on Growth Performance of Nursery Pigs - C. B. Carpenter; J. C. Woodworth; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz; J. Usry (Kansas Agricultural Experiment Station Research Reports, 2016)
A total of 665 pigs [Group 1; 350 barrows (DNA 200 × 400; initially 14.1 lb)] and [Group 2; 315 barrows and gilts (DNA 241 × 600; initially 11.4 lb)] were used to determine the effects of added Cu source and level on nursery pig performance. There were 5 pigs per pen and 10 replications per treatment in group 1 and 5 pigs per pen and 9 replications per treatment in group 2. Pens of pigs were allotted by BW to 1 of 7 dietary treatments arranged as a 2 × 3 factorial plus a control diet, with main effects of Cu source (IntelliBond-C; Micronutrients, Indianapolis, IN or Mintrex-Cu; Novus, St. Charles, MO) and Cu level (75, 150, or 225 ppm). Diets were corn-soybean meal-based and were fed in meal form in 2 phases (d 0 to 14 and 14 to 35). All diets contained a trace mineral premix formulated to contribute 17 ppm of Cu from CuSO4in the complete diet. Overall (d 0 to 35), there were no Cu source × level interactions observed. Increasing Cu increased ADG (linear, P = 0.048) and final BW (linear, P = 0.019). The increase in ADG with no effect on ADFI resulted in a tendency for improved F/G (linear, P = 0.091) with increasing added Cu in the diet. There were no effects of Cu source on growth performance. Because the growth effects were linear, it is unknown from our study if increasing added Cu beyond 225 ppm would further improve growth.
Keywords: nursery pig; copper; copper amino acid-complex; tri-basic copper chloride